A City of Brand Names: (En)Countering Narratives of Development in Qingdao, China Tourism - Wilson, Scott (InTensions, 2009)
This paper examines how promotional tourist DVDs construct narratives of corporate space in Qingdao, China. The videos - which are marketed at heritage tourist sites as “video postcards” - are designed to produce a particular chronotope in which the industrialization of Qingdao’s hinterlands emerges inevitably from the landscapes of heritage tourist sites. These spatial narratives are directed at domestic tourists, and take advantage of distinctly Chinese traditions of image-making and tourism. By narrating the connections, for example, between Mount Lao (the birthplace of Taoism) and the Tsingtao Breweries (China’s most famous brand name), the videos and associated tours “place” the body of the tourist in past-time spaces of Chinese heritage, contemporary (imagined) landscapes of unproblematic development, and projected, “branded” landscapes of Qingdao’s (and China’s) future.